Sustainability Analysis of Limestone Industrial Area Bukit Tui Kota Padang Panjang (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims toanalyze the sustainability of the Bukit Tui area of Padangpanjang City in a multidimensional manner based on ecological, economic, social, institutional and technological dimensions. The data used are primary data, analyzed using a multidimensional scaling (MDS) analysis approach, developed into the Rapfish (Rapid Appraisal of Fisheries) application, Leverage analysis and Monte Carlo analysis and secondary data obtained from the results of field conservation and literature review and related agencies. This research consists of 38 attributes from five dimensions, namely ecological, economic, social, technological and institutional dimensions. The results showed: based on calculations using the multidimensional scalling method, it was formulated that the sustainability status of the Bukit Tui area was multidimensionally in the fairly sustainable category with a value of 50.60 on a sustainability scale of 0-100, with a stress value of 0.132 and R2 0.95. Each dimension has a fairly sustainable sustainability value with a range of values between 41.68 to 54.21. The ecological dimension has the lowest sustainability value, which is 41.68 is included in the less sustainable category and the institutional dimension has the highest sustainability value, which is 54, 21 is included in the moderately sustainable category, then followed by the technological dimension 41.98 is included in the less sustainable category, the social dimension is 52.10 and the economic dimension is 52.83 is included in the moderately sustainable category